Chlorella’s transport inhibition: A powerful defense against high ammonium stress - Lihe Xu; Li Chen; Longxing Jiang; Jingni Zhang; Peike Wu; Wenguo Wang (Ecotoxicology and Environmental Safety)
Ammonium (NH₄⁺) is a primary nitrogen source for many species, yet NH₄⁺-rich wastewater presents a substantial risk to environment. Chlorella sorokiniana is widely recognized for wastewater treatment. The development of high NH₄⁺ tolerant strains has the potential to significantly enhance wastewater treatment efficiency and reduce treatment costs. This study reports the identification of a C. sorokiniana strain designated hact (high ammonium concentration tolerance). This strain demonstrates a remarkable tolerance to NH₄⁺ (1000 mg/L). Integrative analyses of physiology, metabolomics, and transcriptomics demonstrated that transport inhibition is the principal resistance mechanism against high NH₄⁺ stress in C. sorokiniana. Notably, under elevated NH₄⁺ conditions, the hact strain maintained robust intracellular homeostasis. In contrast, the wild-type (WT) strain exhibited suppressed metabolic activity, reactive oxygen species (ROS), and an excess of detrimental metabolites such as amines. This research enriches our understanding of microalgal molecular responses to high NH₄⁺ stress, paving the way for the development of engineered optimization strategies for microalgal bioremediation systems treating NH₄⁺-rich wastewater.